Primigravida aged pregnancy - Maradiegue, Eduardo (2015)
OBJECTIVE: To determine the maternal perinatal morbility and mortality in the first pregnancy of the older women. MATERIAL AND METHODS: Retrospective and transversal study of 133 older women 35 years old or more who had their first pregnancy attended at Cayetano Heredia National Hospital between january 1st and december 31th 1996. They were compared with 5,006 women who had their first pregnancy at of 20 to 29 years old and attended in the same period of time. RESULTS: The incidence of maternal pathology is more frequent in the first pregnancy of older women with a relative risk (RR) 8,55 for previous arterial hypertension, 2,49 for eclampsia, 1,39 for pre eclampsia, 2,18 for cephalopelvic disproportion and 2,03 for hemorragia of third trimester of pregnancy. Cesarean section has a relative risk of 2,55. For the newborn the relative risk is highter for hyalina membrane (4,09), neonatal apnea (3,47), hyperbilirrubinemia (3,71), and congenital defects (1,5). The maternal mortality rate in older women was 751,9 x 100, 000 newborns and the rate for women 20 to 29 years was 172,3. The perinatal mortality rate type I was 29,6 per 1,000 newborns for the women and 19,6 in these women 20 to 29 years.